Unimodal experience constrains while multisensory experiences enrich cognitive construction - Bremner, A; Spence, C (2008)
Mareschal and his colleagues argue that cognition consists of partial representations emerging from organismic constraints placed on information processing through development. However, any notion of constraints must consider multiple sensory modalities, and their gradual integration across development. Multisensory integration constitutes one important way in which developmental constraints may lead to enriched representations that serve more than immediate behavioural goals. © 2008 Cambridge University Press.